Quality by Design Approach for Development and Characterization of Granisetron Hydrochloride-Loaded Orodispersible Films - Li, Ming-Yan; Wang, Bing; Zhang, Jun-Qi; Yang, Liu-Liu; He, Jun-Tao; Chen, Fang (Pharmaceutical Fronts, 2023)
Granisetron hydrochloride can be used to prevent and treat nausea and vomiting induced by chemotherapy. Its prolonged half-life and reduced dose requirement improve patient acceptance. However, patients undergoing chemotherapy often suffer from dysphagia and drug spitting due to emesis. Hence, the development of a patient-centered formulation of granisetron hydrochloride with simple medication and high compliance is crucial. The current study employed a polymer combination of polyvinylpyrrolidone/polyvinyl alcohol (PVP/PVA) as film-forming materials and Lycoat® RS 780 as a disintegrant to formulate orodispersible films (ODFs) loaded with granisetron hydrochloride. Guided by the concept of quality by design, the quality target product profile and critical quality attributes (CQAs) for the ODF were defined. Through the quality risk assessment, essential factors that have a significant impact on CQAs were identified. The formulation was screened using the Box–Behnken statistical design with three factors and three levels. Our data suggested that all ODF formulations exhibited a disintegration time of less than 60 seconds and complete dissolution within 5 minutes. Furthermore, the formulation displayed appropriate mechanical properties, water residue, and pH values. Thus, the granisetron hydrochloride-loaded ODF is regarded as a patient-friendly formulation that enhances compliance and consequently aids in therapeutic effectiveness.
Keywords: granisetron hydrochloride; orodispersible films; quality by design